A Two-Level Factorial Design for Screening Factors that Influence the Decolorization of Congo Red by Serratia marcescens strain Neni-1 - Rusnam, .; Rahman, M.F.A.; Khayat, Mohd Ezuan; Rahim, Mohd Badrin Hanizam Abdul; Manogaran, Motharasan; Yakasai, Hafeez Muhammad (Journal of Environmental Microbiology and Toxicology, 2023)
The toxicity and persistence of Congo Red pollution make it a major threat to both the environment and human health. Biodegradation, which involves the breakdown of pollutants by microbes like bacteria, fungi, and algae, is an attractive and long-term solution to the problem of Congo Red pollution. Optimization techniques such as Response Surface Methodology can further improve biodegradation processes' efficiency, but initial screening is often needed. Using a two-level factorial design, this study successfully screened five parameters (temperature, pH, incubation time, concentration of Congo Red, and sucrose) that affect Congo red's decolorization by Serratia marcescens strain Neni-1. Additionally, it identified three significant parameters that contribute to optimized decolorization of Congo Red: pH, incubation time, and the concentration of Congo Red. Various diagnostic plots were used to analyze the important contributing factors or parameters, including ANOVA, Pareto's chart, and perturbations plot. The two-level factorial conclusion was supported by diagnostic plots such as half-normal, residual vs runs, Cook's distance, Box-Cox, leverage vs runs, DFBETAS, and DFFITS. Consistent with trends in the published literature, this study found that the majority of Congo Red-degrading microorganisms thrive in nearly neutral environments. In future works, RSM can be used to further optimize the parameters that contributed to the decolorization of this bacterium on Congo Red.